2004
DOI: 10.1002/app.20470
|View full text |Cite
|
Sign up to set email alerts
|

Structure and morphology of an intumescent polypropylene blend

Abstract: This article deals with the study of the efficiency of different compatibilizing agents in the intumescent polypropylene/polyamide-6/ammonium polyphosphate (PP/PA-6/APP) blend. The migration of additive was first investigated by X-ray photoelectron spectroscopy. The study showed that ethylene-butyl acrylate-maleic anhydride is not efficient in preventing the exudation of APP to the surface. However, ethylene vinyl acetate (EVA) prevented such a phenomenon. Second, the modifications in the blends were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…While migration is also driven by the interfacial tension between additive and matrix, the use of a compatibilizer can reduce its rate. Almeras et al have observed that EVA (with 24 wt% of vinyl acetate) prevents the exudation of APP during processing in PP/PA6/APP blends . Nevertheless, in another study, the same group noted that EVA fails to prevent APP exudation during weathering (as already discussed above).…”
Section: How To Limit the Influence Of Ageing On Flame Retardancymentioning
confidence: 87%
“…While migration is also driven by the interfacial tension between additive and matrix, the use of a compatibilizer can reduce its rate. Almeras et al have observed that EVA (with 24 wt% of vinyl acetate) prevents the exudation of APP during processing in PP/PA6/APP blends . Nevertheless, in another study, the same group noted that EVA fails to prevent APP exudation during weathering (as already discussed above).…”
Section: How To Limit the Influence Of Ageing On Flame Retardancymentioning
confidence: 87%
“…Dipentaerythritol (DPER) and tripentaerythritol (TPER) with lower water‐solubility but higher price were used as a charring agent in intumescent systems,13 but the migration and thermal instability problems still remained. On the other hand, some macromolecular charring agents such as polyamide (PA) and TPU were adopted 14–17. Bugajny et al16,17 found that TPU as a char‐forming polymer possessed better stability in the PP/APP/TPU intumescent system, but, unfortunately, poorer flame retardancy than using PER as the charring agent in this system.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Furthermore, studies have focused on intumescent flame retardancy for polyolefins by using charring polymers such as PA6 as the carbonization agent. [11][12][13][14][15][16] In this work, we investigated the intumescent flame retardant system of ABS/PA6/SMA alloys with APP in which APP acted as an acid source and a blowing agent and PA6 as a carbon source. Furthermore, we employed various synergistic charring agents to investigate the synergistic effect of charring agents on the flame retardancy of ABS/PA6/SMA blends.…”
Section: Introductionmentioning
confidence: 99%